Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3233/wor-141904
|View full text |Cite
|
Sign up to set email alerts
|

Development and prevention of work related disorders in a sample of Brazilian violinists

Abstract: The use of inadequate strategies and the lack of appropriate options to deal with risk factors contributed to the maintenance of symptoms or the onset of health disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
0
11
0
7
Order By: Relevance
“…For some publications, we could not find a specification of the exact time frame used by the study, f.e. (Lima et al 2015;Blackie et al 1999;Crnivec 2004;De Smet et al 1998;Eller et al 1992;Fishbein et al 1988;Fry 1986;Schäcke et al 1986;Hodapp et al 2009;Kim et al 2012;Kovero and Könönen 1995;Middlestadt 1990;Middlestadt andFishbein 1988, 1989;Molsberger 1991;Papandreou and Vervainioti 2010).…”
Section: Period Of Time Investigated In Cross-sectional Studiesmentioning
confidence: 99%
“…For some publications, we could not find a specification of the exact time frame used by the study, f.e. (Lima et al 2015;Blackie et al 1999;Crnivec 2004;De Smet et al 1998;Eller et al 1992;Fishbein et al 1988;Fry 1986;Schäcke et al 1986;Hodapp et al 2009;Kim et al 2012;Kovero and Könönen 1995;Middlestadt 1990;Middlestadt andFishbein 1988, 1989;Molsberger 1991;Papandreou and Vervainioti 2010).…”
Section: Period Of Time Investigated In Cross-sectional Studiesmentioning
confidence: 99%
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%
“…Dois dos músicos atendidos se dedicavam à regência, 11 (9%) ao canto e os demais (89%) eram instrumentistas, incluindo os que tocavam mais de um instrumento musical. Os instrumentos mais frequentes foram violão (25), violino (11), percussão (10), contrabaixo acústico (9), piano (8), guitarra (8) e violoncelo (6).…”
Section: Quais Os Resultados Até O Momento?unclassified
“…Os fatores de risco para o surgimento de distúrbios osteomusculares têm como determinantes a organização do trabalho e da produção, a concepção de ferramentas e equipamentos, o ambiente físico, a inadequação do mobiliário, a sobrecarga de trabalho, postura inadequada e estresse emocional, gerados pela elevada exigência de si mesmo, pelo medo de falhar e pelas dificuldades interpessoais no trabalho 3,4,11,13,17 . Para reduzir os fatores de risco de modo mais efetivo seria necessário atuar em todos estes determinantes de forma integrada.…”
Section: Considerações Finais E Perspectivas Futurasunclassified
See 1 more Smart Citation